Algorithms for Particle-Field Simulations with Collisions - Sigurgeirsson, Hersir; Stuart, Andrew; Wan, Wing-Lok (Journal of computational physics, 2001)
We develop an efficient algorithm for detecting collisions among a large number of particles moving in a velocity field, when the field itself is possibly coupled to the particle motions. We build on ideas from molecular dynamics simulations and, as a byproduct, give a literature survey of methods for hard sphere molecular dynamics. We analyze the complexity of the algorithm in detail and present several experimental results on performance which corroborate the analysis. An optimal algorithm for collision detection has cost scaling at least like the total number of collisions detected. We argue, both theoretically and experimentally, that with the appropriate parameter choice and when the number of collisions grows with the number of particles at least as fast as for billiards, the algorithm we recommend is optimal.